Siemens eBus Strategy for the Czech Market - Lébrová, Jana; Lhotáková, Markéta, 1971-; Růžička, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
Vehicles that use unconventional power sources have been consecutively implemented in a public transportation with the aim to replace conventionally fuelled vehicles. Based on regulations stated by the European Union in the White Book, it is clear that the total number of them will increase, because those using petrol or diesel will not be able to fulfill them. However, high investments in technology and its development are needed. These investments are reflected in purchasing price of vehicle, which is about twice bigger than a price of conventionally fuelled one. Because the European Union encourages purchases of alternatively fuelled vehicles, it also financially supports them through the programs such as CIVITAS or ROP. One of the companies that entered the market of alternatively powered vehicles is Siemens AG that is a power and industrial giant. In consortium with the Italian company Rampini Carlo S.p.A, they have developed fully electric bus that is charged from overhead wires. Twelve of these Siemens-Rampini eBuses have been already implemented in daily operations in Vienna. Due to this implementation, Vienna became the first European city with a line fully served by eBuses. Therefore, the strategy of successful implementation created by Siemens AG Österreich (Austria and CEE market) for CEE market is used as a hint for Siemens, s.r.o. (the Czech Republic) with the aim to adapt strategy based on the factors found in the Czech market and then apply it in the Czech Republic.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses